Three-Dimensional LIFT Model A Gifted-Talented High School Program - Ellis, Donna Logue; Natchitoches Parish School Board, LA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
A model for a high school program for gifted/talented students is presented. Career exploration is emphasized in grade 9 while career choices are narrowed from four in grade 10 to two in grade 12 with an apprenticeship in one career choice. Curriculum concentrates on communication and media in grade 9, the physical universe in grade 10, humanities in grade 11, and touchstones (philosophy, psychology, and the fine arts) in grade 12. Goals and objectives of the model are listed along with a brief description of evaluation. The bulk of the document is composed of appendixes, including sample lesson plans. (CL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Career Awareness; Career Choice; Career Education; Career Exploration; Curriculum; Gifted; High Schools; Models; Talent; Reports, Descriptive